Teachers’ Reflection towards Current Issues on Grammar Teaching and Learning: EFL Teachers Voices - Dwi Bayu Saputra (English Department - University of Sultan Ageng Tirtayasa, 2020)
This study aimed to explore EFL teachers‟ beliefs towards teaching and learning grammar with the help of some reflective questions. Reflection is alleged to be the utmost beneficial tool to help teachers to discover their beliefs; it is thought to be able to improve their classroom practices as well. In this study, the participants were 30 teachers teaching English at some senior high schools in Bandung. The data collections were gathered through questionnaires and interviews. The initial consisted of 20 statements concerning grammar teaching and the latter has conducted in the form of an in-depth interview to gain more information from the participants. The finding indicates that the participants did well in reflecting on the issue of grammar teaching and they were able to articulate their beliefs on the matters being investigated; the choices whether to choose explicit grammar teaching or implicit grammar teaching differ among participants. Based on these findings, the teachers should be able to create meaningful practices such as combining both implicit and explicit grammar teaching so that the students can always be motivated to learn due to the diverse ways of delivering materials.